2020
DOI: 10.1038/s41598-020-57659-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for miRNA isolation and quantification from ovine plasma

Abstract: c. purdie & Karren M. plain microRNA (miRNA) are promising candidates for disease biomarkers as they are abundant in circulation, highly stable in biological fluids and may yield diagnostic biomarker signatures. The reported issues with miRNA isolation using traditional RNA reagents necessitates the optimisation of miRNA isolation from challenging samples. In this study we compared six commercial RNA extraction kits to evaluate their ability to isolate miRNA from ovine plasma. We also compared three methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…This indicates that the Qubit measurements were more consistent for RNA extracted from a larger plasma volume, given it is within the limit of saturation. Good performance of Qubit from 200-µl plasma has also been observed in another recent study 40 .…”
Section: Discussionsupporting
confidence: 72%
“…This indicates that the Qubit measurements were more consistent for RNA extracted from a larger plasma volume, given it is within the limit of saturation. Good performance of Qubit from 200-µl plasma has also been observed in another recent study 40 .…”
Section: Discussionsupporting
confidence: 72%
“…It has been identified that a number of factors including RNA isolation and detection systems can contribute to this inconsistency. Recently published work from one laboratory, which used different commercial kits to isolate RNA, demonstrated that the recovery of RNA was variable between the commercial kits (El-Khoury et al, 2016;Wright et al, 2020). In addition, the selection of endogenous controls to normalize the target miR expression levels directly affects the results, and such importance has been neglected by some studies.…”
Section: Overall Challenges Of Using Secreted Mirs To Predict Implantmentioning
confidence: 99%
“…Sample quality and processing are important factors affecting the quality and quantity of cfRNAs. Pre-analytical and analytical aspects should be considered since physiological processes such as blood hemolysis of blood during plasma collection can influence the measurement of cfRNAs [ 60 , 61 ]. The methods used for the isolation of exosomes also can also affect the quality of exosomal miRNA profiles [ 51 ].…”
Section: Methodologies For Liquid Biopsymentioning
confidence: 99%